2020
DOI: 10.1002/term.3139
|View full text |Cite
|
Sign up to set email alerts
|

Nanographene oxide‐calcium phosphate to inhibit Staphylococcus aureus infection and support stem cells for bone tissue engineering

Abstract: Staphylococcus aureus (S. aureus) is a major pathogen for osteomyelitis. Calcium phosphate bone cement (CPC) paste is promising for orthopedic uses. Nanostructured graphene oxide (GO) showed antibacterial effect on Gram‐positive bacteria. However, there has been no report of incorporating GO into CPC. The objectives of this study were to (a) develop an injectable and mechanically strong CPC‐chitosan paste containing GO and (b) investigate the inhibition of S. aureus infection and the promotion of human umbilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The addition of GO could improve the antibacterial property of bone cement and prevent the formation of bacterial biofilm, represented by Staphylococcus and E. coli. Biomaterials with CP/GO/chitosan scaffolds are expected to be excellent candidates for bone tissue engineering (Wu et al, 2020;Xie et al, 2016).…”
Section: Antimicrobial Mechanisms Of Gms In Bone Tissue Engineeringmentioning
confidence: 99%
“…The addition of GO could improve the antibacterial property of bone cement and prevent the formation of bacterial biofilm, represented by Staphylococcus and E. coli. Biomaterials with CP/GO/chitosan scaffolds are expected to be excellent candidates for bone tissue engineering (Wu et al, 2020;Xie et al, 2016).…”
Section: Antimicrobial Mechanisms Of Gms In Bone Tissue Engineeringmentioning
confidence: 99%
“…For CPC-chitosan-GO paste, the GO nano powder (XFNANO Materials Tech, Nanjing, China) was mixed with the CPC-chitosan paste to obtain a final GO concentration of 50 μg/mL. The composite disks were prepared as previously described in specific molds [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to our previous study [ 9 ], the capacity of CPC-chitosan scaffold with or without GO for hDPSCs support was determined by live/dead assay for 1 day, 3 days, and 5 days culture. The percentage of live hDPSCs were examined and calculated for stem cell support.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[198,199] Due to the existence of GFMs, bGBMs also present antibacterial properties. [177,[200][201][202][203][204][205][206] Moreover, the introduction of GFMs realizes the sustained release of loaded drugs and bioactive molecules. [173,182,184,[207][208][209][210] Since many articles demonstrated that the osteogenic potential of GBMs persisted even in the absence of chemical inductors, researchers tried to explore the underlying mechanotransduction.…”
Section: Osteoinductivitymentioning
confidence: 99%